Migrant entrepreneurs in Germany: Which role do they play? - Tanja El-Cherkeh; Andreia Tolciu (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
In recent years, self-employment among migrant groups has increased significantly in Germany. Against this background, this article aims at presenting an overview of recent entrepreneurial developments. By drawing on a wide range of secondary literature and statistical data, the present survey places the topic into a broad historical and socio-economic context. Furthermore it raises policy-oriented questions and discusses new directions for research.
Keywords: 330; migrant entrepreneurs; labour market integration; legal provisions; entrepreneurial developments